Let me entertain you?: Some reflexions on the professor as a DJ - Biehl-Missal, Brigitte (Organizational Aesthetics, 2015)
Imagine night clubs, ecstatic crowds and a DJ’s pounding bass lines. And now think of a lecture theatre. You see any parallels yet? Well, how about that a DJ is nothing when the crowd does not dance, and a professor is unhappy when students, er, don’t feel entertained? On the dark side of the aesthetic development of education to be considered in this editorial there is a definite trend towards entertainment: the portemanteau word "edutainment" refers to both education and entertainment and has received critique as some teachers seem to invest more effort in entertaining students rather than educating them (Billsberry, 2014).